Study on Performance Analysis of Luo Converter with Fuzzy Controller - et. al., R. Logasri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
DC/DC converter occupies a major parte in generation of electric power from Renewable Energy Resources (RES). However, because of varying weather nature, the conventional converter exhibits poor conversion efficiency. Thus, this work proposed a Positive Output Luo Converter to have increased conversion efficiency. To extract maximised power from a PV system, P and O tracking system has been implemented. Thus, the performance of this proposed converter with FLC is examined using MATLAB. The results clearly stated that this proposed topology has higher ability to extract maximum power from a PV and thus reveals higher efficiency.